Office collaboration system - Ishak, Azimah (2005)
In today’s competitive market, having fast access to accurate information can be crucial for the business. Office Collaboration System enables of sharing and disseminating up-to-date information which it is a web-based application that facilitates collaboration. Office Collaboration System could store information and be securely accessed from anywhere, anytime, anyplace to improve communication between employees in various remote sites. The study aims to bring about the changes, development and better improvement to the organizational through the effective use of computer technology in terms of information management to provide value and service to the client. Office Collaboration System is built upon the JavaServer Pages (JSP) and Java Servlets technologies. JavaServer Pages allows Web and application designers and developers to create information-rich and dynamic Web pages. Key components of Office Collaboration System are Interactive & Collaborative Communication, Knowledge Assets & Document, Content Management and Workflow Automation. Testing is a crucial part of any system development and implementation. It is to ensure that all components of the system are reliable and robust, and the system delivered matches the user's requirements. The Change Management is to be implemented continuously at the organizational to support the new system environment which likely to have radical change from the current system environment. With the new system environment, new procedures and work culture requires an extensive training to be incorporated.